Comparative outcomes of elderly and non‐elderly patients receiving first‐line palliative chemotherapy for advanced biliary tract cancer. Issue 2 (February 2014) - Kou, Tadayuki; Kanai, Masashi; Ikezawa, Kenji; Ajiki, Tetsuo; Tsukamoto, Tadashi; Toyokawa, Hideyoshi; Yazumi, Shujiro; Terajima, Hiroaki; Furuyama, Hiroaki; Nagano, Hiroaki; Ikai, Iwao; Kuroda, Nobukazu; et al.
Abstract Background and Aim Few studies have reported the efficacy and safety of palliative chemotherapy in elderly patients with advanced biliary tract cancer. We aimed to investigate the clinical outcomes of palliative chemotherapy for advanced biliary tract cancer in elderly patients. Methods We retrospectively evaluated 403 consecutive patients who received palliative chemotherapy between April 2006 and March 2009 for pathologically confirmed unresectable or recurrent biliary tract cancer. Clinical outcomes of the elderly group (≥ 75 years old; n = 94) were compared with those of the non‐elderly group (< 75 years old; n = 309). Results Except for the extent of disease, patient baseline characteristics were well balanced between both groups. The median overall survival was 10.4 months in the elderly group and 11.5 months in the non‐elderly group (hazard ratio, 1.14; 95% confidence interval, 0.89–1.45; P = 0.31). Although the frequency of adverse events between both groups was similar, interstitial pneumonitis was significantly more frequent in the elderly group than in the non‐elderly group (4.3% vs 0%, P < 0.01). Conclusions In advanced biliary tract cancer, overall survival of elderly patients receiving palliative chemotherapy is comparable with that of non‐elderly patients. To our knowledge, this is one of the largest studies that have reported the clinical outcomes of elderly patients following palliative chemotherapy.